Huntington's disease is a four-repeat tauopathy with tau nuclear rods - Fernández-Nogales, Marta; Cabrera, Jorge R; Santos-Galindo, María; Hoozemans, Jeroen J M; Ferrer, Isidro; Rozemuller, Annemieke J M; Hernández, Félix; Avila, Jesús; Lucas, José J (Nature medicine, 2014)
Tau pathology is identified in brains of individuals with Huntington's disease (HD), and reduction of tau expression can ameliorate disease in HD model mice. An imbalance of tau isoforms containing either three or four microtubule-binding repeats causes frontotemporal dementia with parkinsonism linked to chromosome 17 (FTDP-17) in families with intronic mutations in the MAPT gene. Here we report equivalent imbalances at the mRNA and protein levels and increased total tau levels in the brains of subjects with Huntington's disease (HD) together with rod-like tau deposits along neuronal nuclei. These tau nuclear rods show an ordered filamentous ultrastructure and can be found filling the neuronal nuclear indentations previously reported in HD brains. Finally, alterations in serine/arginine-rich splicing factor-6 coincide with tau missplicing, and a role of tau in HD pathogenesis is evidenced by the attenuation of motor abnormalities of mutant HTT transgenic mice in tau knockout backgrounds.